(untitled) (Sustainability in Debate, 2019)
Disaster risk warnings have been issued by the National Centre for Monitoring and Early Warning of Natural Disasters (Cemaden) to municipalities susceptible to floods and landslides in Brazil since December 2011. A survey of the end-users was developed in order to obtain an evaluation related to quality, anticipation and precision of the warnings. Using an explorative approach, a semi-structured questionnaire was available online to be filled in by the individuals responsible for receiving the warnings. The analysis of the results was supported by statistical techniques, to allow association among the variables. The majority of the users did not report difficulties in understanding the warning texts. However, they reported the inefficiency in receiving warnings by email and suggested that faster tools would be a better solution, i.e. a short message service. The improvements in the alerts could be informed by the results achieved in this survey.